PENGARUH PEMBERIAN JAMUR Fusarium graminearum TERHADAP HISTOPATOLOGI TUBULUS SEMINIFERUS MENCIT (Mus musculus) - Kabayo, Fierda; Samik, Abdul; Ismudiono, Ismudiono; Restiadi, Tjuk Imam; Soeharsono, Soeharsono; Plumeriastuti, Hani (Universitas Airlangga, 2019)
The aim of this research was to show the influence of seminiferous tubules histopathology of mice (Mus musculus) caused Fusarium graminearumexposure. This research was done in April-May 2017 in Microbilogy Laboratory Faculty of Science and Technology, Animal Laboratory, and Microbilogy Laboratory Faculty of Veterinary Medicine UniversitasAirlangga. This research used 20 male mice (Mus musculus) aged 6 weeks with 18-30 gram body weight. The mice devided into four groups: P0 given 0,25 ml Sodium chloride without Fusarium graminearum exposure by oral; P1 given 0,25 ml Fusarium graminearum exposure with dilution 102 by oral; P2 given 0,25 ml Fusarium graminearum exposure with dilution 103 by oral; and P3 given 0,25 ml Fusarium graminearum exposure with dilution 104 by oral. This treatment carried out for 21 days. Each milliliter dilution containing 228x106 spore for P1, 228x107 spore for P2, and 228x108 spore for P3. Then do the surgery and harvesting the testes then performed histopathological examination by scoring of seminiferous tubules. For data analyzing used non parametric difference Kruskall-Wallis and continued with Mann-Whitney. The result of this research was showed that decreased the spermatogenic cells in the process of spermatogenesis significant.